Manajemen Pelibatan Orang Tua untuk Meningkatkan Mutu Hasil Belajar Peserta Didik - Suliaswati, Suliaswati; Ainun Frilia Rahayu, Ainun Frilia Rahayu; Puspita Komala, Puspita Komala; Tresna Ayu Ratnapuri Zulfitri, Tresna Ayu Ratnapuri Zulfitri; Yosal Iriantara, Yosal Iriantara (PT. Solusi Komunikasi Terapan, 2024)
Parental involvement plays an important role in encouraging learning outcomes. However, the average level of parental involvement is still low. This research aims to obtain an overview of the management of parental involvement in school programs to improve the quality of student learning outcomes including planning, organizing, implementing and evaluating. The method used is descriptive qualitative. To analyze the data, we refer to George R Terry’s management theory and Morrison’s concept of parental involvement. Research findings show that parent involvement starts from planning various programs with analysis of schedules and financing; organizing includes the formation of a program management team, student groups and parent groups; implementation includes the implementation of parent involvement in various school events; evaluation includes reflection and follow-up plans. From the results of this research, it was concluded that the efforts made by schools to involve parents were realized in various programs and had an impact on increasing academic and non-academic achievement.